Development of New Vaccines against Meningococcal Disease - Bröker, Michael (Arzneimittelforschung, 2003)
Meningococcal diseases continue to have a major public health impact in many countries. Five major groups of Neisseria meningitidis (A, B, C, Y and W135) are responsible for most meningococal diseases. Plain polysaccharides vaccines for Neisseria meningitidis groups A, C, Y and W-135 have been in use for approximately 20 years, both to prevent invasive disease in high-risk population and to control disease outbreaks. However, these conventional meningococcal vaccines induce a relatively short-lasting T-cell independent immune response, are not effective in children under two years of age and can induce hyporesponsiveness. New meningococcal group C conjugate vaccines have since been developed, which offer solid advantages over the currently licensed plain polysaccharide vaccines. There is still no vaccine available against the serogroup B, which is a major cause of invasive disease. This report summarises the different approaches to the development of vaccines against the pathogenic meningococci.
Keywords: Meningococcal epidemiology; Meningococcal vaccines; Polysaccharide antigens, conjugates, outer membrane vesicles, recombinant proteins; Vaccinology, reverse